A study on the design of fully-integrated RF CMOS low-noise amplifiers for 2.4 GHz application - Manlangit, Edmund Cornelius Vargas (2007)
In this thesis, the methodology on the design of fully-integrated RF CMOS low noise amplifier (LNA) satisfying near-standard specifications is presented. In order to satisfy the design constraints, several design techniques like (1) matching for maximum available gain, (2) matching for constant-gain, (3) simultaneous noise and input matching (SNIM), (4) gain-enhancement, (5) bias and width adjustment for high linearity and (6) matching for stability were used. Using a 0.25 CMOS process, 24 LNA test circuits, 12 of which are fully integrated and the other 12 circuits are externally-biased, employing the common-source topology with cascode configuration were implemented and fabricated. The supply-independent and constant-gm biasing circuits were utilized to set the dc bias conditions of the LNAs. Analysis and simulation results show that depending on the desired LNA performance, the proper choice of design technique can be used to satisfy the design constraints. It was also shown that the gain-enhancement technique is a very practical way of increasing the gain of an LNA without degrading the noise figure. The SNIM technique could yield lower noise figures for LNAs while using the bias and width adjustments techniques for LNAs could produce highly linear LNAs. The matching for stability technique is an effective way of making an initially unstable LNA unconditionally stable. Also, discrepancies were observed between S-parameter simulation results and results obtained from on-wafer testing.